2019
DOI: 10.3748/wjg.v25.i4.485
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of endoscopic sphincterotomy vs open choledochotomy for common bile duct stones

Abstract: BACKGROUNDEndoscopic sphincterotomy (EST) for the management of common bile duct stones (CBDS) is used increasingly widely because it is a minimally invasive procedure. However, some clinical practitioners argued that EST may be complicated by post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis (PEP) and accompanied by a higher recurrence of CBDS than open choledochotomy (OCT). Whether any differences in outcomes exist between these two approaches for treating CBDS has not been thoroughly e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…However, there is little data on whether there is a difference between the two methods in the treatment of CBDS. Zhou et al (98) concluded that compared with OCT, EST was superior to OCT in terms of duration of relief of biliary obstruction, duration of anesthesia, duration of surgery, and hospitalization days. However, there was no significant difference between OCT and EST in the recurrence and mortality of choledocholithiasis.…”
Section: Est Vs Ocbdementioning
confidence: 99%
“…However, there is little data on whether there is a difference between the two methods in the treatment of CBDS. Zhou et al (98) concluded that compared with OCT, EST was superior to OCT in terms of duration of relief of biliary obstruction, duration of anesthesia, duration of surgery, and hospitalization days. However, there was no significant difference between OCT and EST in the recurrence and mortality of choledocholithiasis.…”
Section: Est Vs Ocbdementioning
confidence: 99%
“…Laparoscopic common bile duct exploration (LCBDE) and open choledochotomy (OCT) are usually indicated when patients are suspected of having cancer or removal of CBDS when ERCP has failed . LCBDE has a shorter hospital length of stay than OCT or two‐stage treatment (ERCP and cholecystectomy) .…”
Section: Introductionmentioning
confidence: 99%
“…Minimally invasive treatment of CBDS has the advantages of safety, quick recovery, less pain, and less economic burden. LCBDE and EST [ 17 ] are the main minimally invasive operation for the treatment of CBDS, and the curative effect is satisfactory. However, there is no consensus on the medium and long-term complication difference between the 2 operations.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 , 13 ] Both EST and LTCBDE could effectively treat CBDS with high success rates. [ 14 , 15 ] However, there are few studies about the differences of medium and long-term complications after EST or LTCBDE. Therefore, we will conduct a meta-analysis and systematic review to systematically evaluate the difference of medium and long-term complications between EST and LTCBDE against CBDS.…”
Section: Introductionmentioning
confidence: 99%